Diagnostic accuracy of a novel and rapid lipoarabinomannan test for diagnosing tuberculosis among people with human immunodeficiency virus - Bjerrum, Stéphanie; Denkinger, Claudia M. (Open Forum Infectious Diseases, 2020)
AbstractBackground. The novel Fujifilm SILVAMP TB-LAM (FujiLAM) assay detects mycobacterial lipoarabinomannan in urine and has demonstrated superior sensitivit